Clinical features and treatment outcome of borderline resectable pancreatic head/body cancer: a multi‐institutional survey by the Japanese Society of Pancreatic Surgery. Issue 6 (August 2013) - Kato, Hiroyuki; Usui, Masanobu; Isaji, Shuji; Nagakawa, Takukazu; Wada, Keita; Unno, Michiaki; Nakao, Akimasa; Miyakawa, Shuichi; Ohta, Tetsuo
Abstract Background Optimal treatment types and prognosis for patients with borderline resectable pancreatic cancer (BRPC) remain unclear because of the lack of studies involving large series of patients. Methods We retrospectively analyzed various prognostic factors for 624 BRPC (pancreatic head/body) patients treated from June 2002 to May 2007, by distributing questionnaires to member institutions of the Japanese Society of Pancreatic Surgery in 2010. BRPC was defined according to the National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines (2009). Results Among 624 patients, 539 (86.4 %) underwent curative‐intent resection, showing an R0 resection rate of 65.9 %. The 3‐ and 5‐year survival rates were 16.1 and 9.9 % in all patients, 22.8 and 12.5 % in the resected patients, and 4.4 and 0 % (P < 0.0001) in the unresected patients, respectively. The following factors influencing survival in all patients were selected as independent prognostic factors using multivariate analysis: major arterial involvement on imaging study; preoperative treatment; surgical resection; and postoperative chemotherapy. Among the resected cases, multivariate analysis revealed that major arterial involvement and remnant tumor status were independent prognostic factors. Conclusion BRPC included two distinct categories of tumors influencing survival: those with portal vein/superior mesenteric vein invasion alone and those with major arterial invasion, which was the most exacerbating factor in the analysis.